2020
DOI: 10.4103/ajir.ajir_25_20
|View full text |Cite
|
Sign up to set email alerts
|

Uneventful sleeve gastrectomy post bariatric arterial embolization

Abstract: We present the case of a 42-year-old female patient who successfully and uneventfully underwent gastric sleeve surgery 3-years after left gastric artery embolization, for the treatment of obesity. This case highlights that left gastric artery embolization may not preclude future bariatric surgeries in this subset of patients who initially fail to lose weight after bariatric arterial embolization (BAE).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 9 publications
(10 reference statements)
0
1
0
Order By: Relevance
“…There have been three patients described in the literature who successfully had bariatric surgeries (two sleeve gastrectomy, and one gastric plication) after BAE. 59 Although insufficient alone, these observations support continued clinical inquiry.…”
Section: Future Directionsmentioning
confidence: 77%
“…There have been three patients described in the literature who successfully had bariatric surgeries (two sleeve gastrectomy, and one gastric plication) after BAE. 59 Although insufficient alone, these observations support continued clinical inquiry.…”
Section: Future Directionsmentioning
confidence: 77%
“…Further studies need to clarify this aspect, but recent studies show promising results in this regard. One study reported an uneventful SG surgery three years post BAE [ 42 ]. In Reddy et al, two patients underwent a bariatric surgical intervention (SG and laparoscopic gastric plication) post BAE to further leverage weight loss and experienced no perioperative or postoperative complications [ 25 ].…”
Section: Discussionmentioning
confidence: 99%